HUBUNGAN JARAK TEMPAT TINGGAL DAN POLA KUNJUNGAN PASIEN DENGAN PEMANFAATAN PUSKESMAS PUTRI AYU KOTA JAMBI - Viona Rahma Pratama; Erna Elfrida Simanjuntak; Fransiska Br. Sitepu (Journal of Hospital Administration and Management (JHAM), 2026)
​​ Access to healthcare services is one of the important factors influencing the utilization of community health centers (Puskesmas). Residential distance and patient visit patterns are considered to play a role in determining the level of healthcare service utilization at Putri Ayu Community Health Center, Jambi City. This study aimed to determine the relationship between residential distance and patient visit patterns with the utilization of Putri Ayu Community Health Center, Jambi City. This study employed a quantitative method with an analytical observational design using a cross-sectional approach. The population consisted of patients residing within the working area of Putri Ayu Community Health Center, Jambi City, during the period of January–December 2025. The total population was 35,640 patients, and a sample of 100 respondents was selected using the accidental sampling technique. Data were collected using a questionnaire and analyzed through univariate and bivariate analyses using the Chi-Square test with a 95% confidence level (α = 0.05). The results showed that most respondents lived close to the community health center (91 respondents; 91%), had regular visit patterns (96 respondents; 96%), and utilized the community health center services (94 respondents; 94%). Bivariate analysis revealed that there was no significant relationship between residential distance and the utilization of Putri Ayu Community Health Center, Jambi City (p-value = 0.499 > 0.05). However, patient visit patterns were significantly associated with the utilization of Putri Ayu Community Health Center, Jambi City (p-value = 0.000 < 0.05). In conclusion, residential distance was not significantly associated with the utilization of Putri Ayu Community Health Center, whereas patient visit patterns were significantly associated with its utilization.